Valoração econômica ambiental do Parque Nacional Montanhas do Tumucumaque: uma aplicação do Método de Valoração Contingente - Ferreira Júnior, Eduardo Braz Barros (2021)
The processes of economic valuation of ecosystem goods and services in recent decades have gained increasing space for discussion as a result of concerns generated in the current scenario of exploitation and degradation of natural resources. In this sense, the need is highlighted in the search for human behavior patterns, as well as instruments that can help decision-making processes that involve the sustainable use of natural resources. Therefore, it became necessary to reformulate the conceptualization of the economic value associated with natural spaces that considers an internalization of externalities and an optimal intergenerational allocation of resources, incorporating the preferences of individuals and their levels of well-being captured by the use of goods and ecosystem services. Based on these assumptions, this study aims to estimate the Total Economic Value of the set of ecosystem goods and services offered by the Tumucumaque Mountains National Park (PNMT), through the application of the Contingent Valuation Method. The methodology used was based on the application of the Stated Preferences Method, from the use of a binary logistic regression model to estimate the Willingness to Pay (DAP) of the interviewed public, considering a set of explanatory variables, such as: economic, sociological and psychological contributions, and their respective marginal contributions. In obtaining the Economic Value of the Total Park, other complementary methods were used, such as: Avoided Costs Method, Market Price Methods and Benefits Transfer Method. As a research instrument, a questionnaire was applied from a simple stratified probabilistic sampling with proportional allocation. An optimal sample size of 167 respondents was obtained, which are represented by eight municipalities in a total of nine that cover the PNMT area, considering the proportional allocation criterion. The environmental economic valuation developed in the Park provided a Total Economic Value (VET) of R$16.062.553.242,47, which corresponds to the Value in Use (VU) of R$15.927.316.277,69, divided into Direct Use Value (VUD) R$2.260.299,87, Indirect Use Value (VUI) R$15,925,055,977.82, Recreational Use Value (VUR), R$34,136.95. For the Non-Use Value (VNU) the Existence Values (VE) and Legacy Values (VL) were identified, corresponding to R$135,236,964.79. The results obtained represent a tool to support the formulation of public policies, management plans and environmental studies in Amapá, which is the Brazilian state with the highest percentage of environmental preservation and is home to the largest tropical forest park in the world, the Montanhas do Tumucumaque.